(3OjhGf GdTQja GdYbjdj (B((3GHf MjOQI(B)s - (3CHhGdMSf Ydj Hf GdMSjf Hf MjOQI Hf eMeO Hf YHO Gddg Hf eMeO,J (B450 (3g` s ((3CMeO Hf CdjGS s)
(3ChdgG (B:s
(3bGd CHhGdMSf Ydj Ydi bGajI GdCda(B: (3jGSjOG eG Kfi YfGfG eP cGf Yf SeYg GdKfGA s
(3BNQgG (B:s
(3hNqQHrJ UQhag eG YeQG aGdMeO ddg Ydi eG bOQG gPG BNQ TYQ CHj GdMSf GdYbjdj GdeUQj s
(3GfXQ GdLRA GdChd HQbe (B242 (3COH HYfhGf(B: (3OjhGf GHf MjOQI GdYbjdjs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B89s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B519 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B130 s
Keywords: (3GdCOHs